Kinetik und Mechanismus der selektiven Bindung von Ionen durch Cyclodepsipeptid-Antibiotika - Th. Funck; F. Eggers; E. Grell (CHIMIA)
Stability constants for cation complexes of valinomycin and enniatin B were determined in methanol employing spectrophotometric titrations. Kinetic studies by relaxation methods led to the elucidation of the reaction mechanism of complex formation. Complexation of valinomycin with cations follows a multistep reaction characterized by two relaxation times. The rate constants observed for complex formation of approximately 107 M-1s-1 are remarkably small compared to diffusion controlled reactions and correspond to the rate constants of the slow conformational changes of the uncomplexed depsipeptide. Therefore, the rate limiting step of cation complexation is a ligand conformational change which occurs during the step-wise subsitution of solvent molecules from the cation. Differences in the rates of complex formation of valinomycin with sodium and potassium ions are significant for the mechanism of ion selectivity which is related to conformational properties.